Problems and Prospects of Tourism in Bangladesh Bandarban District Case (Global Journal of Management and Business Research, 2013)
Tourism is an emerging sector for Bangladesh. Tourism is one of the most growing industries all around the world. Bandarban is one of the district of bangladesh that is blessed with unparallel devine beauty. There are more than sixteen popular tourist spot at Bandarban in Bangladesh. In 2011, 1036 foreign tourist sand in 2012, 1205 foreign tourists came Bandarban to visit and enjoy its natural beauty. The aim of this paper to reveals the problems and prospects of tourism at Bandarban. The writer tried to highlight the special attractive tourist spots of Bandarban. These papers also find out some barriers of tourism at Bandarban and provide some suggestions to overcome those problems.
Keywords: Tourism; Nature; Bandarban; Domestic tourist; Foreign tourist